2021
DOI: 10.15537/smj.2021.42.8.20210236
|View full text |Cite
|
Sign up to set email alerts
|

Early infection in post-autologous hematopoietic stem cell transplant patients

Abstract: Results:The study findings indicate that bacterial infection prevalence differed significantly across the different disease status pre-salvage as patients with the relapsed disease were more likely to have bacterial Original Articleinfections. The median of engraftment days differed significantly between those who had a bacterial infection and those who did not. Interestingly, previous pneumonia infection had a positive relationship with the number of hospital stays. Conclusion:Bacterial infections are the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…Other than COVID-19, no viral infections were identified among the patients who underwent autologous HSCT in this study. The findings were consistent with those reported in a recent study in Saudi Arabia [ 17 ]. These findings could be explained by the recent improvements in screening measures to ensure serological clearance before transplantation and the use of prophylactic antiviral agents.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Other than COVID-19, no viral infections were identified among the patients who underwent autologous HSCT in this study. The findings were consistent with those reported in a recent study in Saudi Arabia [ 17 ]. These findings could be explained by the recent improvements in screening measures to ensure serological clearance before transplantation and the use of prophylactic antiviral agents.…”
Section: Discussionsupporting
confidence: 93%
“…Clostridium difficile and Escherichia coli were the most prevalent gram-positive and gram-negative microorganisms, respectively. The findings reported in this study were consistent with those reported in regional studies in Saudi Arabia and Lebanon and those reported in St. Jude Children’s Research Hospital [ 17 , 26 , 27 ]. Additionally, Clostridium difficile infections were shown to be prevalent among patients who underwent autologous HSCT in Johns Hopkins Hospital in the US and Hôpital Maisonneuve-Rosemont in Canada [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Not all auto-HCT indications are associated with the same infection risk, and germ cell tumour patients are an understudied group due to the rarity of the condition. Indeed, most studies investigating infections after auto-HCT describe patients with lymphomas and multiple myeloma [11–14]. Our large cohort from a specialist referral centre allowed us to showcase that auto-HCT recipients with germ cell tumours had a higher risk of bacteraemia compared to these traditional transplant indications.…”
Section: Discussionmentioning
confidence: 96%